Self-Driven Bioelectrochemical Mineralization of Azobenzene by Coupling Cathodic Reduction with Anodic Intermediate Oxidation. (1st February 2015) - Liu, Rong-Hua; Li, Wen-Wei; Sheng, Guo-Ping; Tong, Zhong-Hua; Lam, Michael Hon-Wah; Yu, Han-Qing
Graphical abstract: Highlights: Azobenzene was reduced to aniline at the cathode of an acetate-fueled MFC. Aniline was degraded at the bioanode of a single-chamber MFC. Cathodic reduction of azobenzene was coupled with anodic oxidation of aniline. Self-driven, complete mineralization of azobenzene in an MFC was accomplished. Abstract: Bioelectrochemical systems have been intensively studied as a promising technology for wastewater treatment and environment remediation. Coupling of the anodic and cathodic electrochemical reactions allows an enhanced degradation of recalcitrant organics, but external power supply is usually needed to overcome the thermodynamic barrier. In this work, we report a self-driven degradation of azobenzene in a microbial fuel cell (MFC), where the cathodic reduction of azobenzene was effectively coupled with the anodic oxidation of its reduction degradation intermediate (i.e., aniline). The anodic degradation rate of aniline, as the sole carbon source, was significantly higher than that under open-circuit conditions, suggesting a considerable bioelectrochemical oxidation of aniline. Output voltages up to 8 mV were obtained in the MFC. However, a shift of cathodic electron acceptor from oxygen to azobenzene resulted in a decreased aniline degradation rate and output voltage. The present work may provide valuable implications for development of sustainable bioelectrochemical technologies for environmental remediation.